A vicious partnership between AKT and PHLDA3 to facilitate neuroendocrine tumors. Issue 6 (22nd May 2017) - Takikawa, Masahiro; Ohki, Rieko
Abstract : Pancreatic neuroendocrine tumors (PanNET) are rare cancers that generally have a poor prognosis. Accurate diagnosis and proper treatment of these tumors requires a better understanding of the molecular mechanisms underlying the development of PanNET. It has been shown that the mTOR inhibitor everolimus can improve the progression‐free survival of PanNET patients, suggesting that inhibition of the PI3K‐Akt‐mTOR pathway may suppress the progression of PanNET. PHLDA3 is a novel tumor suppressor protein that inhibits Akt activation by competition for binding to PIP3 . Our analysis of PanNET revealed frequent loss‐of‐heterozygosity and DNA methylation at the PHLDA3 locus, resulting in strong suppression of PHLDA3 transcription. Such alterations in the PHLDA3 gene were also frequently found in lung neuroendocrine tumors (NET), suggesting the possibility that various types of NET have in common the functional loss of the PHLDA3 gene. Abstract : Neuroendocrine tumors (NET) are rare cancers, and a better understanding of the molecular mechanisms underlying the development of NET is required for accurate diagnosis and proper treatment of these tumors. It has been shown that the PI3K‐Akt‐mTOR pathway plays an important role in pancreatic NET tumorigenesis, and we previously have shown that PHLDA3, a repressor of Akt, functions as a novel tumor suppressor of pancreatic and lung NET. In this paper, we review some recent findings regarding the significance and molecular modes of action of PHLDA3 and Akt in neuroendocrine tumors.